2015
DOI: 10.1177/102490791502200406
|View full text |Cite
|
Sign up to set email alerts
|

How Accurate are Emergency Department Medical Staff in the Interpretation of Head Injury Related Computed Tomography?

Abstract: How accurate are emergency department medical staff in the interpretation of head injury related computed tomography?急診科醫務人員在判讀與頭部受傷相關的電腦斷層掃描有多準確呢? LW Cheung 張立援, YN Shih 史有毅, CS Leung 梁展新, WS Lo 盧詠琛, M Leung 梁明, ACH Lit 列就雄 Introduction: Computed tomography (CT) brain has become a popular modality to detect head injury related problems for patients seen at the Emergency Departments (ED) in Hong Kong. This study aims to assess the diagnostic accuracy of local ED medical staff in interpretation of head injury r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
(21 reference statements)
0
1
0
Order By: Relevance
“…Among the remaining 10 studies, only Al-Reesi et al 11 and Cheung et al 16 conducted retrospective reviews and found the concordance between ED and the final radiology report to be 0.93 (95% CI 0.91 to 0.95) and 0.91 (95% CI 0.90 to 0.92), respectively. The eight studies that obtained data prospectively had significantly heterogeneous methods in regards to whether the ED interpretation was documented freehand or on a standard template, the blinding of participants to the clinical indication for the scan and the level of training of the participants.…”
Section: Discussionmentioning
confidence: 99%
“…Among the remaining 10 studies, only Al-Reesi et al 11 and Cheung et al 16 conducted retrospective reviews and found the concordance between ED and the final radiology report to be 0.93 (95% CI 0.91 to 0.95) and 0.91 (95% CI 0.90 to 0.92), respectively. The eight studies that obtained data prospectively had significantly heterogeneous methods in regards to whether the ED interpretation was documented freehand or on a standard template, the blinding of participants to the clinical indication for the scan and the level of training of the participants.…”
Section: Discussionmentioning
confidence: 99%